Surgical Staging for Cervical Cancer - Hadwin, Richard; Olaitan, Adeola (Current Women's Health Reviews, 2011)
Cervical cancer presents a significant challenge for the clinician in choosing the optimal therapy. The majority of disease burden remains in the resource poor developing world, where sophisticated surgical or radiological staging is generally not available. In the developed world, surgery remains the mainstay of treatment for early invasive disease, but surgical staging is of controversial importance in the management of later stage disease. Evolution of minimal access techniques have reduced the mortality and morbidity for the techniques, and may shift the emphasis from radiological to surgical approaches. We discuss the available methods used for surgical staging for cervical cancer, the evidence supporting these techniques and their relative merits.
Keywords: Cervix cancer